Challenges Encountered by Grade 12 Performing Art Students in Bestlink College of the Philippines, S.Y. 2019–2020 in Making Theater Production: Basis for Crafting Guidelines (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
Theater is a collaborative form of fine arts that uses live performance, typically using actors or actresses, to present the experience of a real or imagined event before a live audience in a specific place (often a stage). Performers may communicate this experience to the audience through the combination of gestures, speech, song, music, and dance. The elements of art, such as painted scenery, and stagecraft, such as lighting, are used to enhance the physicality, presence, and immediacy of the experience. The specific place of the performance is also named by the word “theater,” which is derived from the ancient Greek word “theatron,” which means “a place for viewing,” and itself form “theaomi,” which means “to see,” “to watch,” or “to observe. Qualitative research was used as the research design for the study. Purposive sampling was utilized to gather respondents who assess the challenges encountered by Grade 12 Performing Arts students of Bestlink College of the Philippines, S.Y. 2019–2020 in making theater production based on crafting guidelines. The study has used an instrument of survey questionnaire conducted by the researchers to gather data from the two groups of respondents. Results indicate that respondents’ mean for the challenges encountered in making theater production as to academic performance. Respondents’ mean for the challenges encountered in making theater production as to academic performance. The overall weighted means of 3.64 and 3.76 of male and female respondents strongly agreed with their incapability to accomplish school tasks. The average of 3.57 for male respondents showed strongly agree, and the average of 3.78 for female respondents strongly agreed. With the weighted means of 3.64 and 3.42, the male respondents showed strongly agree, while female agreed that the lack of time to go to school is a challenge for them. Respondents strongly agreed that they cannot participate in school, with the means of 3.86 and 4.44. Last, the weighted mean of 3.50 for male respondents showed strongly agree, while the weighted mean was 3.44 for female respondents in terms of focusing on class. The subsequent recommendation about the study was to adapt to the challenges that they experiencing in making theater productions, such as performing on the stage, doing rehearsals, and looking in the mirror when practicing to boost their self-confidence. When challenges or problems are encountered, always see it as a lesson or new learning.
Keywords: theater, performing arts